Threshold and interaction effects in the trade, growth, and inequality relationship - Vincent Leyaro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper examines the relationship between trade (exports), growth, and inequality, using a panel of 100 countries over 30 years (1980 to 2010). As there is no clear theoretical relationship between trade (exports) and inequality, and as inequality can be considered a proxy for 'governance quality', the paper also tests for a threshold in inequality for the effect of trade (exports) on growth. The findings are that in general trade openness advances growth while inequality reduces growth. However, when we identify an inequality threshold, we find that inequality is positively associated with growth if below the threshold (low inequality) but negative above the threshold, whereas trade has a positive impact once the threshold is allowed for. Thus, trade generally promotes growth and relatively high inequality retards growth.
Keywords: F10; I31; O40; 330; trade; growth; inequality; threshold effects